HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN BUDAYA ORGANISASI DENGAN KINERJA GURU SEKOLAH MENENGAH PERTAMA NEGERI DI GUGUS LURAGUNG KABUPATEN KUNINGAN - Rasidin Rasidin; Disman Disman; Pupu Saeful Rahmat (Universitas Kuningan, 2022)
ABSTRACT This study aims to examine the relationship between the principal's transformational leadership and organizational culture on teacher performance in junior high schools. This study uses an explanatory survey research method. Where the research data was taken on 113 respondent teachers spread over 6 schools in the Luragung Junior High School Cluster. The research instrument uses a questionnaire technique using a rating scale. The data obtained were then processed using descriptive statistical techniques. Hypothesis testing using regression test and multiple regression test with the help of path analysis. The conclusions from the results of this study are (1) there is a positive correlation between the principal's transformational leadership and the performance of Junior High School teachers in the Luragung Cluster, Kuningan Regency, and (2) there is a positive correlation between organizational culture and teacher performance in Junior High Schools in the Luragung Cluster, Kuningan Regency. (3) There is a positive correlation between the principal's transformational leadership and organizational culture together with the performance of teachers in Junior High Schools in the Luragung Cluster, Kuningan Regency.Keyword : Transformational Leadership; Organizational Culture; Teacher PerformanceABSTRAKPenelitian ini bertujuan untuk meneliti hubungan antara kepemimpinan transformasional kepala sekolah dan budaya organisasi terhadap kinerja guru di Sekolah Menengah Pertama. Penelitian ini menggunakan metode penelitian survei eksplanasi (explanatory survey). Dimana data penelitian diambil terhadap 113 orang guru responden yang tersebar pada 6 sekolah di SMP Negeri Gugus Luragung. Instrumen penelitian menggunakan teknik kuesioner menggunakan rating scale. Data yang diperoleh kemudian di olah dengan menggunakan teknik statistik deskriptif. Pengujian hipotesis dengan menggunakan uji regresi dan uji regresi berganda dengan bantuan path analisis. Kesimpulan dari hasil penelitian ini adalah (1) terdapat korelasi positif antara kepemimpinan transformasional kepala sekolah dengan kinerja guru Sekolah Menengah Pertama Negeri di Gugus Luragung Kabupaten Kuningan (2) Terhadap korelasi positif antara budaya organisasi dengan kinerja guru di Sekolah Menengah Pertama Negeri di Gugus Luragung Kabupaten Kuningan (3) Terdapat korelasi positif antara kepemimpinan transformasional kepala sekolah dengan budaya organisasi secara bersama-sama dengan kinerja guru di Sekolah Menengah Pertama Negeri di Gugus Luragung Kabupaten KuninganKeyword : Kepemimpinan transformasional; Budaya organisasi, Kinerja Guru